REKONSTRUKSI HUKUM KELUARGA ISLAM MELALUI INTEGRITAS MAQASID AL-SYAR’IAH DAN PRINSIP HAM DI INDONESIA - Hendrianto; Marbujang; Herliansyah, Putrado; Anro Foza, Yerry; Suyatna, Enang (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This research explores the potential integration of maqāṣid al-sharī‘ah with human rights principles (HAM) as a conceptual basis for advancing the modernization of Islamic family law in Indonesia. Through a qualitative–descriptive method grounded in library-based investigation, the study examines a range of primary references such as the Qur’an, Hadith, the Compilation of Islamic Law (KHI). The results indicate that maqāṣid al-sharī‘ah align closely with the core values upheld by human rights, especially concerning justice, the preservation of human dignity, and the promotion of societal welfare Moreover. In conclusion, the study provides a meaningful contribution by outlining a theoretical and practical model for reforming Islamic family law into a system that is more human-oriented, inclusive, and responsive to human rights concerns. At the same time, it enhances the relevance and standing of Islamic law within Indonesia’s national legal structure.